Effect of Catharanthus roseus, Kalanchoe laciniata and Piper longum extracts on the proliferation of hormone-dependent breast cancer (MCF-&) and colon cancer (Caco2) cell lines - Rahmat, Asmah; M. Z., Zeeti Nadia; Md Akim, Abdah; Abu Bakar, Mohd Fadzelly (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
This research was conduted to investigate the effect of canthranthus roseus (Kemunting Cina), Kalanchoe laciniata (Setawar Kampung) and (kadok kampung) on the in vitro proliferation of hormone dependent breast cancer (MCF-7) and colon cancer (Caco2) cell lines. Methodology: the effects of canthranthus roseus, Kalanchoe laciniata and piper longum (hexane, chloroform, ethyl acetate and methanol extracts) on the cytotoxicity of MCF-7 and Caco2 cell lines were measured using (3-[4,5=dimethylthiazol-2-yl]-2,5-diphenyultetrazoluimbromide) (MTT) assay. Results: Kalanchoe laciniata hexane extract showed significant inhibitions on MCF-7 carcinoma cell lines proliferation with IC 50 value of 75.7 μg/ml. canthranthus roseus extracts (hexane, chlofoform and ethyl acetate) inhibited MCF-7 cells proliferation at concentrations of 80, 70 and 90 μg/ml, respectively. Discussion: IC50 value of all extracts of piper longum and Kalanchoe laciniata chloroform and ethyl acetate and methanol extracts on the proliferation of MCF-7 cancer cells could not be determined, as it did not demonstrate any appreciable inhibition on the cellular proliferatin at the concentration tasted. However, piper longum chlofofrom and ethyl acetate extracts showed anti-tumourigenic effect against colon cencer (Caco2) woth IC50 of 87 μg/ml and 20μg/ml, respectively. Kalanchoe laciniata hexane extarcts inhibited Caco2 cellular proliferation with IC50 value of 100μg/ml. Canthranthus roseus chlofofrom and ethyl acetate extracts inhibited Caco2 proliferation at IC50 of 28.2 μg/ml and 74.1 μg/ml, respectively. Conclusion: From this study, it can be concluede that only hexane extaract of Kalanchoe laciniata was effective against cellular prolifirations of MCF-7 while piper longum was more effective in inhibiton Caco2 proliferation. However, both the herbs were not so effective against MCF-7 and Caco2 cell lines compared with canthranthus roseus.